Protection Technology of Motor of Model 12CM15 Continuous Shearer - QU Fu-hai (Gong-kuang zidonghua, 2011)
The paper introduced various electrical and mechanical protection technologies of motor of model 12CM15 continuous shearer, and expounded problems which should be paid attention to in routine maintenance.